Self-suspended starch fluids for simultaneously optimized toughness, electrical conductivity, and thermal conductivity of polylactic acid composite. (5th January 2019) - Yu, Qiao; Li, Yun; Han, Lu; Yin, Xianze; Xu, Jing; Zhou, Yingshan; Chen, Dongzhi; Du, Zhengliang; Wang, Luoxin; Tan, Yeqiang
Abstract: It is challenging to fabricate a starch derivative with a plasticizing effect and good dispersion in a poly(lactic acid) matrix to achieve desirable performance. In this study, self-suspended starch fluids composed of modified granules as the core and polyethylene glycol-substituted tertiary amines as the shell were first fabricated via a combined carboxymethylation and acylation reaction. The as-prepared starch fluids exhibited liquid-like behavior and had semiconductor electric conductivity (4.91 × 10 −5  S/cm) at room temperature without a solvent. The modulus of starch fluids was clearly reduced under the heating process and exhibited its initial flow properties upon cooling, displaying thermo-reversible behavior. The resultant fluids were then incorporated into a poly(lactic acid) matrix to produce fully biodegradable composites with desirable performance. At a loading level of 10 wt%, starch fluids exhibited simultaneous enhancements in elongation at break (increase of 164.7%) and thermal conductivity (increase of 119%) of PLA composites compared to pure PLA, attributable to the good dispersion and heat-transfer properties of starch fluids. In addition, PLA composites with 10 wt% loading of starch fluids demonstrated excellent antistatic performance (3.08 × 10 −4  S/cm), suggesting that polar groups of the PLA structure and PEG groups of starch fluids contributed synergistically to the electrical conductivities of composites. These results indicate that starch fluids are promising antistatic agents and plasticizers for potential applications in biodegradable materials.